Is drawing from the state ‘state of the art’?: a review of organised crime research data collection and analysis, 2004–2018 - Windle, James; Silke, Andrew (Springer, 2019)
This paper presents a systematic review of organised crime data collection and analysis methods. It did this by reviewing all papers published in Trends in Organized Crime and Global Crime between 2004 and 2018 (N = 463). The review identified a number of key weaknesses. First, organised crime research is dominated by secondary data analysis of open-access documents, and documents are seldom subjected to the same principles guiding primary data collection methods. Second, data analysis lacked balance with a distinct lack of inferential statistical analysis. Third, there was a significant absence of victim or offender voices with an overreliance on data from state bodies and the media. The paper concludes that organised crime, as field of research, appears unbalanced by reliance upon a small number of methods and sources. Rebalancing the field requires more organised crime researchers to speak to offenders and victims, employ greater use of statistical analysis and tighten our methodologies.
Keywords: Organised crime; Research methods; Data analysis; Data collection; Interviews; Ethnography; Victims